Multi-criteria decision-making methods for preliminary design of sustainable facades. (September 2018) - Moghtadernejad, Saviz; Chouinard, Luc. E.; Mirza, M. Saeed
Abstract: The current design and construction trends toward sustainable development have led to increased attention on designing high performance building structures, especially emphasizing reductions in energy consumption and CO2 emissions. Facades have the potential to drastically affect building energy performance and the comfort level of occupants; therefore, more attention and effort needs to be given to their design than at present. However, the involvement of various interdisciplinary professionals and the need for satisfying different design criteria makes the design process considerably complicated. This complexity is related to the required integration and provision for balance between all necessary functions of a façade system, which can be conflicting with each other. Consequently, most designers still tend to use conventional design methods that lack consideration of all required criteria. Multi-Criteria Decision Making (MCDM) analysis is a useful tool to assist designers with this integration, by generating the best solutions for achieving conflicting and multiple objectives. MCDM methods have been extensively used in management and optimization fields; however, their application to building technology, especially in façade design, is relatively recent. Currently there are many MCDM methods available, each with related benefits and drawbacks. Nevertheless, not all MCDM methods are appropriate for providing solutions to the façade design problem. This paper reviews and compares the most common MCDM methods for façade design. Accordingly, the most efficient methods for sustainable façade design are introduced and used in a decision-making process to examine their efficiency in façade design.